Physiopathological Premises to Nuclear Medicine Imaging of Pancreatic Neuroendocrine Tumours - Cuccurullo, Vincenzo; Di Stasio, Giuseppe D.; Mansi, Luigi (Current Radiopharmaceuticals, 2019)
Background: Pancreatic Neuroendocrine Tumors (P-NETs) are a challenge in terms of both diagnosis and therapy; morphological studies need to be frequently implemented with nonstandard techniques such as Endoscopic Ultrasounds, Dynamic CT, and functional Magnetic Resonance. Discussion: The role of nuclear medicine, being scarcely sensitive F-18 Fluorodeoxyglucose, is mainly based on the over-expression of Somatostatin Receptors (SSTR) on neuroendocrine tumor cells surface. Therefore, SSTR can be used as a target for both diagnosis, using radiotracers labeled with gamma or positron emitters, and therapy. SSTRs subtypes are capable of homo and heterodimerization in specific combinations that alter both the response to ligand activation and receptor internalization. Conclusion: Although agonists usually provide efficient internalization, also somatostatin antagonists (SS-ANTs) could be used for imaging and therapy. Peptide Receptor Radionuclide Therapy (PRRT) represents the most successful option for targeted therapy. The theranostic model based on SSTR does not work in insulinoma, in which different radiotracers such as F-18 FluoroDOPA or tracers for the glucagon-like peptide-1 receptor have to be preferred.
Keywords: nuclear medicine